Multi-injection turbine housing for turbine performance improvement: A numerical and experimental analysis - Liu, Hao (SAGE Publications Ltd, 2021)
Secondary flow injection is a way which allows for the efficiency of a turbomachine to be increased further, after blade design optimizations have already been performed. In this paper, a novel method for improving turbine performance using secondary flow injection through an injection slot over the turbine shroud is investigated. Numerical simulations were conducted on a mixed-flow turbocharger turbine to test the effectiveness of secondary flow injection. An optimization was performed at peak efficiency at 50% turbine design speed to determine the injection setup which gives the highest turbine efficiency. Single-passage simulations for the optimized point showed an increase in efficiency of 2.6 percentage points compared to the baseline turbine. Flow analysis shows that injection partially blocks the flow passage near the blade tip, forcing turbine passage flow to migrate towards the hub. This apparently weakens the hub suction side separation vortex and reduces entropy generation from the vortex. Experimental testing was conducted and used for validation of full-stage turbine computational fluid dynamics (CFD) simulation results. Full-stage turbine CFD results show that with inlet nozzle vanes, secondary flow injection did not result in any visible improvement in the internal flow field and entropy generation, but overall efficiency can be improved by up to 2.28 percentage points at a velocity ratio of 0.75. Without nozzle vanes, however, secondary flow injection resulted in an efficiency improvement of up to 6.79 percentage points by weakening the hub suction side separation vortex and reducing its associated losses. Injection on the vaneless turbine configuration also resulted in a roughly 2 percentage point improvement in the peak turbine efficiency over the vaned turbine configuration. This might be due to more flow energy available to be extracted by the rotor from reduced losses due to the lack of nozzle vanes.